Discovering Sustainability in New York City: An Interdisciplinary Framework for Teaching in Urban Institutions - Pilgrim, Karyn; Woo, Kevin (Journal of Interdisciplinary Studies in Education, 2021)
Ecological learning is enriched when students can apply course content to their own communities and gain an understanding and experience for deploying sustainable practices. Such merging of content, application, and place requires an interdisciplinary approach to grapple with the ecological and cultural issues more holistically that sustainability education explores. Guided by the ecological pedagogy of David Orr, founder of the Oberlin Project, we devised a pilot study that combines course content in environmental science, cultural studies, and writing with place-based, experiential, and hands-on learning to empower students to critically analyze their lifestyles and engage in activism for change.